2001
DOI: 10.1006/jcph.2001.6900
|View full text |Cite
|
Sign up to set email alerts
|

A Cartesian Grid Embedded Boundary Method for the Heat Equation on Irregular Domains

Abstract: We present an algorithm for solving the heat equation on irregular time-dependent domains. It is based on the Cartesian grid embedded boundary algorithm of Johansen and Colella (J. Comput. Phys. 147(2):60-85) for discretizing Poisson's equation, combined with a second-order accurate discretization of the time derivative. This leads to a method that is second-order accurate in space and time. For the case where the boundary is moving, we convert the moving-boundary problem to a sequence of fixed-boundary proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 6 publications
2
135
0
2
Order By: Relevance
“…However, Crank-Nicolson is only neutrally stable, and we found that it led to weak instabilities at coarse-fine interfaces, given the other choices we made in this algorithm. This behavior was similar to that noted at embedded boundaries in [16,20]. To eliminate this problem, we found it necessary to employ a different approach to computing the viscous terms in (1), using the L 0 scheme described in [30].…”
Section: Single-level Time Discretizationsupporting
confidence: 68%
See 1 more Smart Citation
“…However, Crank-Nicolson is only neutrally stable, and we found that it led to weak instabilities at coarse-fine interfaces, given the other choices we made in this algorithm. This behavior was similar to that noted at embedded boundaries in [16,20]. To eliminate this problem, we found it necessary to employ a different approach to computing the viscous terms in (1), using the L 0 scheme described in [30].…”
Section: Single-level Time Discretizationsupporting
confidence: 68%
“…Previous semi-implicit methods have used the Crank-Nicolson scheme to compute the viscous terms in the update. However, for the discretizations used in this work, we found the neutrallystable Crank-Nicolson scheme suffered from weak instabilities at coarsefine interfaces, similar to the behavior noticed at embedded boundaries in [16,20]. To eliminate this problem, we employ a second-order semi-implicit Runge-Kutta scheme based on the L 0 -stable scheme in [30].…”
Section: Introductionmentioning
confidence: 56%
“…The original boundary and the approximated one lie in the same R d−1 space. For example, the following methods can be found in this group: truncated domains methods [6,7], immersed interface methods (I.I.M.) [8,9], penalty methods [1,2,10,11,12,4], fictitious domain methods with Lagrange multipliers [13,14,15], an adapted Galerkin method proposed in [16], and recent work on a fictitious model with flux and solutions jumps for general embedded boundary conditions [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,8,10,15,6,24] and the references herein. Only a few studies have been devoted to embedded Fourier B.C.…”
Section: Introductionmentioning
confidence: 99%
“…Cartesian grid embedded boundary methods introduced in [21] and [32] to increase the geometric flexibility of finite volume methods. Away from the boundaries of the computational domain, this approach uses traditional finite difference discretizations on a regular Cartesian grid.…”
Section: Survey Of Numerical Algorithmsmentioning
confidence: 99%